2014
DOI: 10.4161/19336896.2014.971569
|View full text |Cite
|
Sign up to set email alerts
|

Creutzfeldt-Jakob disease associated with a V203I homozygous mutation in the prion protein gene

Abstract: We report a Japanese patient with Creutzfeldt-Jakob disease (CJD) with a V203I homozygous mutation of the prion protein gene (PRNP). A 73-year-old woman developed rapidly progressive gait disturbance and cognitive dysfunction. Four months after the onset, she entered a state of an akinetic mutism. Gene analysis revealed a homozygous V203I mutation in the PRNP. Familial CJD with a V203I mutation is rare, and all previously reported cases had a heterozygous mutation showing manifestations similar to those of typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
2
5
1
Order By: Relevance
“…Neuropathological examination revealed the presence of abundant multicentric PrP amyloid plaques with mild neuritic component, along with severe neuronal loss, gliosis and microglial proliferation with only mild spongiform change, which is consistent with a GSS neuropathological phenotype. In contrast to previous description of homozygous mutations in PRNP [10][11][12][13]27] (Table 1), the disease in R136S families presented with an autosomal recessive pattern of inheritance, keeping the heterozygous family members protected from developing the disease, at least, at early ages. In vitro propagation and in vivo transmissibility studies suggest that the PrP Sc variant resulting from the R136S mutation failed to propagate both in vivo and in vitro in the conditions analyzed, suggesting that this variant is biologically less active than other mutations causing genetic prion diseases.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Neuropathological examination revealed the presence of abundant multicentric PrP amyloid plaques with mild neuritic component, along with severe neuronal loss, gliosis and microglial proliferation with only mild spongiform change, which is consistent with a GSS neuropathological phenotype. In contrast to previous description of homozygous mutations in PRNP [10][11][12][13]27] (Table 1), the disease in R136S families presented with an autosomal recessive pattern of inheritance, keeping the heterozygous family members protected from developing the disease, at least, at early ages. In vitro propagation and in vivo transmissibility studies suggest that the PrP Sc variant resulting from the R136S mutation failed to propagate both in vivo and in vitro in the conditions analyzed, suggesting that this variant is biologically less active than other mutations causing genetic prion diseases.…”
Section: Discussioncontrasting
confidence: 83%
“…Up to date, all described pathogenic variants cause the disease in heterozygous carriers, being the disease inherited with an autosomal dominant pattern. Very few individuals have been reported to be homozygous for PRNP variants [10][11][12][13]. Most of them are homozygous carriers of well-known pathogenic mutations which cause also the disease in heterozygous carriers from areas of high prevalence of the mutation.…”
Section: Introductionmentioning
confidence: 99%
“…The patient developed progressive gait disturbances and cognitive dysfunctions, followed by akinetic mutism. 49 The clinical phenotypes were similar to the previously described heterozygous cases, but the disease progression was more rapid. 49 This mutation is located in the hydrophobic core of PrP.…”
Section: Summary Of Prion Mutationssupporting
confidence: 82%
“… 49 The clinical phenotypes were similar to the previously described heterozygous cases, but the disease progression was more rapid. 49 This mutation is located in the hydrophobic core of PrP. In silico modeling suggested that it could result in minor effects on prion conformation.…”
Section: Summary Of Prion Mutationssupporting
confidence: 82%
“…Genetic CJD associated with the V203I mutation and homozygosity for Met at codon 129 was first described only with clinical data . Further cases were reported from China and Japan, including a homozygous case for the mutation and neuropathological description of a case . Here we describe three new cases of V203I‐129M, showing classical neuropathological features of CJD.…”
Section: Discussionmentioning
confidence: 79%